2017
DOI: 10.1590/s1519-99402017000200012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of essential oils from Mangifera indica L. cultivars on the antifungal susceptibility of Candida spp. strains isolated from dogs

Abstract: SUMMARY This work reports the chemical study, and anti-Candida spp. activity of leaf essential oil from Mangifera indica cultivars. The essential oils were obtained by hydro-distillation and analyzed by gas chromatography/mass spectroscopy. The anti-Candida spp. activity was evaluated against strains isolated from dogs by the agar-well diffusion method and the minimum inhibitory concentration (MIC) by the broth microdilution method. Tommy Atkins cultivar presented β–selinene (29.49%), caryophyllene oxide (12.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Other constituents that were common in all the four varieties were spathulenol, italicene epoxide, caryphyllene oxide, cyclocolorenone, and humulene epoxide II. This study also reported sesquiterpenoids as the major compound of MLO [ 17 ]. The essential oil from MLs also possesses bacteriostatic properties and contains several antimicrobial constituents such as gurjunene, trans-caryophyllene, humulene, selinene, and camphor.…”
Section: Nutritional Compositionmentioning
confidence: 80%
“…Other constituents that were common in all the four varieties were spathulenol, italicene epoxide, caryphyllene oxide, cyclocolorenone, and humulene epoxide II. This study also reported sesquiterpenoids as the major compound of MLO [ 17 ]. The essential oil from MLs also possesses bacteriostatic properties and contains several antimicrobial constituents such as gurjunene, trans-caryophyllene, humulene, selinene, and camphor.…”
Section: Nutritional Compositionmentioning
confidence: 80%
“…Depending on how the harvesting is performed, this latex can "burn" the peel, which depreciates the commercial value of the fruit (Robinson et al, 1993). A recent investigation addressing the biological properties of the essential oil from the latex of mango has revealed antimicrobial (Fontenelle et al, 2017), antifungal (Perumal et al, 2017), leishmanicidal and cytotoxic (Ramos et al, 2014) properties. However, no studies have investigated the acaricidal potential or the effects on the behavior of Tetranychus urticae Koch (Acari: Tetranychidae).…”
Section: Introductionmentioning
confidence: 99%
“…De la variedad Corazao de boi se hallaron: cipereno (32,62%), (E)-cariofileno (26,91%), α-humuleno (17,12%), terpinoleno (2,32%), β-selineno (5,70%) y mirceno (2,80%). En el mismo año, Fontanelle et al [21] señalaron, como constituyentes principales, para la variedad Tommy-Atkins los siguientes compuestos: β-selineno (29,49%), óxido de cariofileno (12,40%) y epóxido II de humuleno (8,66%); y para las variedades Rosa, Moscatel y Jazmín: óxido de cariofileno (23,62, 48,42 y 30,77%, respectivamente) y epóxido II de humuleno (11,56, 23,45 y 16,27%, respectivamente). Por otra parte, Gebara et al [22] también reportaron altas proporciones de estos compuestos en el aceite esencial obtenido de las hojas de la variedad Coquinho.…”
Section: Resultados Y Discusiónunclassified